The effect of limestone aggregate on the properties of fly ash based geopolymer concrete - Mohd Zulhilmi, Abdul Rahim (2012)
The uses of Portland cement give disadvantages to the nature which is by releasing carbon dioxide gas to the air. This situation can cause global warming at the same time contribute to the greenhouse effect. Besides, the production of Portland cement causes depletion of raw material. In order to solve this problem, the fly ash based geopolymer concrete was produced. This research is focus on the effect of limestone aggregate on the properties of fly ash based geopolymer concrete. The research was done to obtain the optimum proportion of limestone aggregate in fly ash based geopolymer concrete, to determine the effect of limestone aggregate on the characteristic of fresh fly ash based geopolymer concrete and to determine the compressive strength of fly ash based geopolymer concrete with limestone aggregate inclusion. The effect of limestone aggregate as a granite aggregate replacement in geopolymer concrete were investigated 60 numbers of cube dimension 1 OOmm x lOOmm x lOOmm with two difference condition which is 60°c oven and ambient curing for compression test, and 20 numbers of small cube dimension 50mm x 40mm x 80mm for porosity test were prepared. There are five difference mix design which is 0%, 25%, 50%, 7 5%, and 100%. The specimens were tested at the age of 1, 7, and 28 day for compressive strength while for porosity test was at day 28. The slump test for sample 0%, 25%, 50%, 75%, and 100% were 190mm, 205mm, 190mm, 196mm, and 190mm are respectively and all mix sample obtain was collapse slump. Concrete setting time for sample 0%, 25%, 50%, 75%, and 100% was 45 minute, 36 minute, 35 minute, 33 minute, and 25 minute are respectively. The optimum proportion of limestone aggregate in fly ash base geopolymer concrete is 25% for both 60°c oven and ambient curing. The compressive strength at day 28 of sample 0%, 25%, 50%, 75%, and 100% for ambient curing was 19.3Mpa, 26.lMpa, 23.07Mpa, 22.03Mpa, and 17.33Mpa respectively while for 60oc oven curing was 32.02Mpa, 32.77Mpa, 30.94Mpa, 24.46Mpa, and 21.69Mpa respectively.